Corporate behavior and competitiveness: impact of environmental regulation on Chinese firms. (1st January 2015) - Zhao, Xiaoli; Zhao, Yue; Zeng, Saixing; Zhang, Sufang
Abstract: This article presents a structural equation model for exploring the impact of environmental regulations—administrative-based environmental regulation (command-and-control regulation) (AER) and market-based environmental regulation (MER), on Chinese firm behavior and competitiveness on the basis of data collected from Chinese electric power and iron and steel firms (most of these firms are state-owned enterprises). Our results show that both AER and MER promote the firm behavior shift toward green development, and enhance firm competitiveness. However, AER and MER have different impacts on firm specific behaviors such as strategy choice, production decisions, technical progress, and environmental management and different extent of impact on firm competitiveness. In addition, whilst AER has a strong significant positive impact on technological innovation and plays a direct role in competitive improvement, MER does not. On the other hand, only MER plays significant roles in promoting the behavior shift of strategy toward green development. These findings signify that it is important for China to pursue the coordination between AER and MER, and to identify the line of playing roles between AER and MER.